Comparative Study of Biological Properties and Electrophoretic Characteristics of Lipopolysaccharide from Eel-Virulent and Eel-A virulent Vibrio vulnificus Strains - Biosca, Elena G. (American Society for Microbiology, 1999)
In Vibrio vulnificus, virulence for eels is associated with serovar E strains. In this study, we investigated some biological properties of purified lipopolysaccharides (LPSs) from serovar E and non-serovar E strains. Purified LPSs retained their O-polysaccharidic side chains and did not show any differences that could be related to host specificity, except for serological differences.